Des/Memoria histórica y perfromance de identidad en La pequeña historia de Chile - Hernández, Paola (Latin American Theatre Review, 2006)
With a blend of irony and sarcastic humor, Marco Antonio de la Parra exposes his audience to a nostalgic way of thinking about Chile’s new image of a postdictatorial country. In La pequeña historia de Chile, history teachers of a forgotten school reconsider the issues of historical memory, culture, identity and the future of their society in a place where a neoliberal economy has blinded the newer generations. This essay analyzes the role of memory, history and the identity of Chile and its citizenry within the framework of globalization theories. (PSH, in Spanish)